Robotic-assisted unicompartmental knee arthroplasty improves functional outcomes, complications, and revisions - Alessandro Bensa; Alessandro Sangiorgio; Luca Deabate; Andrea Illuminati; Benedetta Pompa; Giuseppe Filardo (2024)
Robotic-assisted unicompartmental knee arthroplasty (R-UKA) has been proposed as an approach to improve the results of the conventional manual UKA (C-UKA). The aim of this meta-analysis was to analyze the studies comparing R-UKA and C-UKA in terms of clinical outcomes, radiological results, operating time, complications, and revisions.